Social Media in Marketing Communication: Strategies for Online Businesses in the Era of Digitalization - Linus, Hamizan; Albert Gisip, Imelda; Harun, Amran (Penerbit UTHM, 2020)
The increasing number of online businesses in digital technology has influenced consumers these past two decades (Alalwan, Rana, Algharabat, & Tarhini, 2016; Dwivedi, Kapoor, & Chen (2015); Rathore, Ilavarasan, & Dwivedi, 2016; Taylor, Lewin, & Strutton 2011; Zhu & Chen, 2015) and many studies have been done by researchers towards social media in marketing communication (Gensler, Völckner, Liu-Thompkins, & Wiertz, 2013; Malthouse, Haenlein, Skiera, Wege, & Zhang, 2013; Tham, Croy, & Mair 2013; Lukka & James, 2014; Liu, Chou, & Liao, 2015; Kumar, Choi, & Greene, 2016). The future explanations will be discussed on the revolution of digitalization in online businesses especially social media impacts marketing outcomes (Clark & Melancon, 2013; Ahmad, Ahmad, & Bakar, 2018; Seo & Park, 2018; Pacauskas, Rajala, Westerlund, & Mäntymäki, 2018) and social media impacts on marketing process (Daou, Sarkis, & Nader, 2018; Iankova, Davies, Archer-Brown, Marder & Yau, 2019; Nunan, Sibai, Schivinski, & Christodoulides, 2018; Effing & Spil, 2016).